2013
DOI: 10.1103/physrevb.87.155139
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of Fabre charge-transfer salts under various temperature and pressure conditions

Abstract: Using density functional theory, we determine parameters of tight-binding Hamiltonians for a variety of Fabre charge transfer salts, focusing, in particular, on the effects of temperature and pressure. Besides relying on previously published crystal structures, we experimentally determine two new sets of structures: (TMTTF) 2 SbF 6 at different temperatures and (TMTTF) 2 PF 6 under various hydrostatic pressures. We find that a few trends in the electronic behavior can be connected to the complex phase diagram … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 47 publications
4
53
0
Order By: Relevance
“…The largest dispersion appears for the paths: Γ → X which is along the stacking direction, U → Γ and Z → R containing contributions of the a-directions as well. The bandwidth for the three materials is about 350 meV for the upper as well as for the lower band, being in excellent agreement with previous studies [13,14]. For the b-direction, the bands are weakly warped and intersect the Fermi energy.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The largest dispersion appears for the paths: Γ → X which is along the stacking direction, U → Γ and Z → R containing contributions of the a-directions as well. The bandwidth for the three materials is about 350 meV for the upper as well as for the lower band, being in excellent agreement with previous studies [13,14]. For the b-direction, the bands are weakly warped and intersect the Fermi energy.…”
Section: Discussionsupporting
confidence: 78%
“…This behavior is similar to applying chemical pressure, already discussed for Figure 12. This observation is supported by calculations of Jacko et al [14] who also observed an increase of the dimensionality when the crystal structure of (TMTTF) 2 PF 6 under hydrostatic pressure was taken for the calculations. Concerning the dimerization, the corresponding gap at the X-point obviously diminishes from 110 meV at 300 K to 55 meV at 100 K, again resembling the effect of pressure as demonstrated in Figure 12.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…For a few decades organic charge-transfer (CT) salts built of donor and acceptor molecular complexes have attracted a lot of attention due to the variety of ground states in their phase diagrams [1][2][3][4][5] . Application of external or chemical pressure can lead to antiferromagnetic insulating, charge ordered, spin-density wave, spin liquid, or unconventional superconducting ground states.…”
Section: Introductionmentioning
confidence: 99%